2014
DOI: 10.1111/sltb.12077
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation and Behavior in Adolescents Aged 12–16 Years: A 17‐Year Follow‐Up

Abstract: The prevalence of suicidal ideation/behavior in 1983 or 1987 and its association with future mental health in 2001 were evaluated in a provincially representative sample of Canadian adolescents (n = 1,248) aged 12 to 16 years. Approximately 13.3% (95% CI = 11.5-15.3) of adolescents self-reported suicidal ideation/behavior. Adolescent agreement with parent (κ = .07) and teacher (κ = .05) reports at baseline was low because adults identified so few subjects. In adulthood, the associations between adolescent self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Among students with depression, we found that the association between perpetration and suicidal ideation was stronger in students with depression than in those without depression. As depression per se was a significant independent risk factor for suicidal ideation, 16 , 17 our results indicated an additive synergism between depression and perpetration on suicidal ideation. However, the associations of victimization and both (victimization and perpetration) with suicidal ideation were weaker in students with depression, compared with those without.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Among students with depression, we found that the association between perpetration and suicidal ideation was stronger in students with depression than in those without depression. As depression per se was a significant independent risk factor for suicidal ideation, 16 , 17 our results indicated an additive synergism between depression and perpetration on suicidal ideation. However, the associations of victimization and both (victimization and perpetration) with suicidal ideation were weaker in students with depression, compared with those without.…”
Section: Discussionmentioning
confidence: 51%
“…Several studies have shown that suicidal ideation is associated with depression in adolescents, 16 , 17 and adolescents involved in bullying are more likely to experience depression. 18 , 19 However, it is unknown whether the association of bullying with suicidal ideation is different in adolescents with and without depression.…”
Section: Introductionmentioning
confidence: 99%
“…Similarily, 33.3% of the cases where parents reported suicidal talk or self-harming behaviors, the child did not report the same (i.e., child underreported symptoms). This discordance between child and parent report of STB is not uncommon and has been documented elsewhere [44][45][46]. Regardless of whether STB are identified when the child initially presents to treatment for anxiety, it should be monitored in an ongoing manner.…”
Section: Discussionmentioning
confidence: 94%
“…It has been demonstrated there is a strong association between suicidal thoughts and depression [ 29 32 ]. Our findings reveal an additive synergism between depression and anorexia nervosa in suicidal thoughts.…”
Section: Discussionmentioning
confidence: 99%